2020
DOI: 10.1016/j.schres.2020.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The “mind” behind the “mask”: Assessing mental states and creating therapeutic alliance amidst COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 11 publications
2
47
0
2
Order By: Relevance
“… Metha et al. (2020) suggested that clinicians use their eyes, eyebrows, hand gestures, and appropriate body postures to facilitate accurate comprehension among patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Metha et al. (2020) suggested that clinicians use their eyes, eyebrows, hand gestures, and appropriate body postures to facilitate accurate comprehension among patients.…”
mentioning
confidence: 99%
“…(2020) suggested that clinicians use their eyes, eyebrows, hand gestures, and appropriate body postures to facilitate accurate comprehension among patients. Research also advised that providing training to clinicians on the correct usage of intonation and prosody to speak clearly through a mask can significantly help build rapport ( Mehta et al., 2020 ). Pamungkasih et al.…”
mentioning
confidence: 99%
“…This study also highlights the impact of the pandemic on anxiety and fear experienced by participants. Future studies are needed to investigate the social and emotional costs of wearing sanitary masks (e.g., for teacher-student and clinician-patient communication as well as for individuals that are hearing-impaired) 16,56 and how bodily postures can compensate for the lack of visible facial features. Follow-up studies are needed in order to monitor the fear and anxiety indicators taking into account potential clinical costs and social implications.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic affected psychiatric care including suicide prevention. Empathic communication is the cornerstone for an effective psychiatric evaluation and treatment 7 . Nowadays, psychiatric patients and psychiatrists are required to wear masks during in‐person visits.…”
mentioning
confidence: 99%